PENGEMBANGAN LKPD BERBASIS GUIDED WRITING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEGAK BERSAMBUNG SISWA KELAS II SD - Salsabila, Dwi Cahya; Kartika Dewi, Galuh; Khusni Mubarok, M. (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2025)
The reason for conducting this research is the problems faced by grade II elementary school students, namely students are less skilled in writing using cursive letters, because there has not been application of special learning media to practice cursive writing and lack of guidance from teachers in practicing writing using cursive letters. This research aims to improve students cursive writing skills through the utilization of LKPD to write upright with friends together. This research applies the research and development method with the ADDIE model. The data collection techniques used include validation from media and material experts, as well as tests. Instruments used in data collection this research is in the form of a media and material expert validation questionnaire, as well as a cursive writing skills test. And the results of this study were calculated using data analysis techniques in the form of media and material feasibility analysis, as well as the N-Gain test. The results showed that the media used obtained an assessment from the media expert of 93%, while the assessment from the material expert 97%, and the final result of validation is 95% with the criteria "very feasible". The results of cursive writing skills students cursive writing skills have increased after using the LKPD to write upright with friends along with the average pre-test score of 69.09 and the average post-test score of 90.00. It can be concluded from the findings of this study that the worksheet (LKPD) for writing upright cursive letters with friends together successfully improved students cursive writing skills, with results that are classified in the high category.